Understanding the Temperature Conditions for Controlled Splicing Between Silica and Fluoride Fibers - Antreas Theodosiou; Ori Henderson‐Sapir; Yauhen Baravets; Oliver T. Cobcroft; Samuel M. Sentschuk; Jack A. Stone; David J. Ottaway; Pavel Peterka (Advanced Photonics Research)
This study explores the efficacy of thermal splicing conditions between silica and zirconium‐fluoride fibers, focusing on achieving mechanical strength between the two fibers. A comprehensive characterization of the thermal profile in the hot zone of the filament splicer was conducted using a fiber Bragg grating, providing valuable insights into its stability and overall performance. Results demonstrate mechanically strong joints and suggest a very narrow temperature window to achieve strong connection between the two materials. Moreover, we characterize the surface composition of the ZrF4 fiber using energy dispersive spectroscopy following splicing at ideal temperatures, as well as at higher and lower temperatures. This work paves the way towards future implementation of silica and fluoride fibers splicing using alternative splicing solutions such as CO2 laser system while raising interesting facts for further studies in the specific field.